Theoretical Modeling of Dielectric Properties of Artificial Shales - Tongcheng Han; Roman Beloborodov; Marina Pervukhina; Matthew Josh; Yanlin Cui; Pengyao Zhi (Geofluids)
Accurately modeling the anisotropic dielectric properties of shales is important for the interpretation of dielectric data acquired from shales as source rocks and unconventional reservoirs. We have developed a multiphase incremental model for the frequency dependent anisotropic dielectric properties of sedimentary rocks and presented an approach based on the developed model to simulate the measured anisotropic dielectric behaviors of artificial shales. The new model was built based on the theoretical basis of differential effective medium models for any number of mineral grain components aligned in any direction and was shown to be independent of the mixing order. The model incorporates the measured orientation distribution function of the clay particles to determine the shale dielectric anisotropy, and the frequency dependent dielectric behaviors of the wet clay minerals are obtained by inverting the dielectric properties of the artificial sample composed of clay and the same brine as in other artificial shales. The modeling technique combined important polarization mechanisms in the intermediate frequency range and was shown to give satisfactory fit to the measured frequency dependent anisotropic relative permittivity and conductivity of the artificial shales with varying silt contents by using a reasonable aspect ratio and constant dielectric parameters for the silt grains.